The importance of early diagnosis of X-linked hypophosphatemic rickets: a case report - Francesca Franchina; Fabio Toscano; Giovanni Luppino; Giorgia Pepe; Tommaso Aversa; Domenico Corica (Atti della Accademia Peloritana dei Pericolanti - Classe di Scienze Medico-Biologiche, 2024)
X-linked hypophosphatemic rickets (XLH) is the commonest inherited form of rickets. XLH is caused by an impaired regulation of fibroblast growth factor 23 (FGF23) due to a PHEX gene mutation, leading to chronic renal phosphate excretion and impairment of vitamin D activation. Children with XLH show clinical signs of rickets, short stature, stunted growth, deformities of the lower limbs, bone and muscular pain, weakness and reduced quality of life.